Pengaruh Model Concept Sentence Terhadap Aktivitas Belajar Siswa Kelas IV SDN Kandangmas Tema 6 Cita-Citaku - Bella Amanda Sari; Siti Masfuah; Imaniar Purbasari (PGSD Universitas Muria Kudus, 2023)
The purpose of this study was to determine the effect of the Concept Sentence model on student learning activities and to test the effectiveness of the Concept Sentence model on student activities in Indonesian and Social Studies content between classes that received treatment with the application of the Concept Sentence model and classes that applied lecture learning on theme 6 My Goals in class IV .This study uses experimental research techniques so that there are experimental and control classes. Using a quantitative approach to the research subject of fourth grade students at SD 2 Kandangmas and SD 5 Kandangmas. Data collection techniques using instruments in the form of observation techniques, documentation techniques and interviews. The data analysis technique used was tested using the t-test at a significant level of 5% and the z test (follow-up test).The results of the hypothesis testing of student learning activities with the results of the T test analysis show that the value of T count T table (9.828 1.98) and the significance value is 0.000 is less than 0.05 (0.000 0.05), so it can be concluded that there is a difference student learning activities using the Concept Sentence model assisted by word card media at SDN Kandangmas. The z test results obtained a z-count of 9.828 with a significance of 0.000. Student activity value z-count z-table 9.828 1.98) and significance (0.000 0.05) then Ho is accepted Ha is rejected. It can be concluded that student activities using the Concept Sentence model are more effective than learning using the lecture method.